2011
DOI: 10.1073/pnas.1110415108
|View full text |Cite
|
Sign up to set email alerts
|

Insights regarding guanine nucleotide exchange from the structure of a DENN-domain protein complexed with its Rab GTPase substrate

Abstract: Rab GTPases are key regulators of membrane traffic pathways within eukaryotic cells. They are specifically activated by guanine nucleotide exchange factors (GEFs), which convert them from their "inactive" GDP-bound form to the "active" GTP-bound form. In higher eukaryotes, proteins containing DENN-domains comprise a major GEF family. Here we describe at 2.1-Å resolution the first structure of a DENN-domain protein, DENND1B-S, complexed with its substrate Rab35, providing novel insights as to how DENN-domain GE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
125
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(133 citation statements)
references
References 36 publications
6
125
0
2
Order By: Relevance
“…Studies in the yeast secretory pathway have shown that Rab GTPases can be sequentially activated via GEF/effector complexes (Ortiz et al 2002). A subset of GEFs could be identified via bioinformatics approaches based on the presence of a conserved DENN domain (Yoshimura et al 2010;Wu et al 2011); however, there are GEF family members that are structurally distinct (Esters et al 2001;Guo et al 2013). Clearly, more factors such as GEFs, GAPs, and effectors coupling the activities of individual and sequentially acting Rab proteins need to be identified and characterized to fully understand how cargo flows between compartments on the endocytic pathway and endocytosis is coordinately up-regulated to address physiological demands.…”
Section: Rab Gtpases On the Endocytic Pathway Compartmentalize Endocymentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in the yeast secretory pathway have shown that Rab GTPases can be sequentially activated via GEF/effector complexes (Ortiz et al 2002). A subset of GEFs could be identified via bioinformatics approaches based on the presence of a conserved DENN domain (Yoshimura et al 2010;Wu et al 2011); however, there are GEF family members that are structurally distinct (Esters et al 2001;Guo et al 2013). Clearly, more factors such as GEFs, GAPs, and effectors coupling the activities of individual and sequentially acting Rab proteins need to be identified and characterized to fully understand how cargo flows between compartments on the endocytic pathway and endocytosis is coordinately up-regulated to address physiological demands.…”
Section: Rab Gtpases On the Endocytic Pathway Compartmentalize Endocymentioning
confidence: 99%
“…First, Rab GTPases undergo cycles of GTP binding and hydrolysis to GDP, which serves to drive a reversible conformational change that is decoded by interacting proteins (Wittinghofer et al 1993). Guanine-nucleotide exchange factors (GEFs) and GTPase-activating proteins (GAPs) catalyze the exchange and hydrolysis reactions and, therefore, act as regulators of the GTP-GDP cycle (Yoshimura et al 2010;Wu et al 2011;Barr 2013;Guo et al 2013;Kotting and Gerwert 2013). Second, Rab GTPases behave both as soluble and specifically localized, integral-membrane proteins.…”
mentioning
confidence: 99%
“…The interaction between a nucleotide-free Rab and a GEF, which is an intermediate step in the activation process, is usually stable, and thus allows their crystal structures to be determined. Thus far, at least five crystal structures of Rab-GEF complexes, i.e., of Rabex5-Rab21, Sec2p-Sec4p, Rabin8-Rab8, TRAPP I-Ypt1p, and DENND1B-Rab35, have been determined, and they provide the structural basis for Rab activation by these GEFs (Delprato and Lambright, 2007;Dong et al, 2007;Sato et al, 2007;Cai et al, 2008b;Wu et al, 2011;Guo et al, 2013). The stable interaction between GEFs and their substrate Rabs can be applied to identifying the substrate specificity of GEFs, e.g., the Rab21-specific GEF Varp specifically interacts with a constitutively negative form of Rab21 and does not interact with constitutively negative forms of 59 other Rabs (Tamura et al, 2009;Mori et al, 2013).…”
Section: Principles Of the Gef-accelerated Gdp-gtp Exchange Reactionmentioning
confidence: 99%
“…It is therefore possible that such uncharacterized longin proteins (e.g., DENN-related protein; see next section) function as In general, a GDP-bound form of Rab is present in the cytosol through interaction with GDI (top). A GEF, a Rab activation enzyme, forms a high-affinity complex with a nucleotide-free form of the Rab (bottom right), and such complexes are often used for crystallographic analysis because of their stability (Delprato and Lambright, 2007;Dong et al, 2007;Sato et al, 2007;Cai et al, 2008b;Wu et al, 2011;Guo et al, 2013). When the Rab binds to GTP, the GEF is released from the Rab (bottom left).…”
Section: Substrates and Functions Of Rab-gefsmentioning
confidence: 99%
See 1 more Smart Citation